The Impact of Switching Costs on Customer Loyalty: A Study among Customers of Mobile Telephony - Allan Ricki; Andreas Raharso (Journal of Applied Finance & Accounting, 2008)
The conditions for doing business are changing rapidly. In last few years the mobile telecom market has witnessed a substantial growth and rapid changes globally as well as domestically. Customer loyalty is a critical issue in the success of any business system, for this reason, the main condition for protecting the subscriber base is to win customer loyalty, a key necessity for the maintenance of a brand’s life in the long term. To achieve this aim, customer loyalty must be measured and “switching costs” identified. The latter render subscribers’ preference for rival operator more expensive. In this connection, this study aim is to measure the impact of switching costs on customer loyalty, and the direct and indirect of “switching costs” on customer loyalty. For doing so, a survey has been performed on customers of the prepaid and postpaid mobile service operator in Indonesia, questionnaire were distributed among them and the results analyzed base upon the proposed research questions and hypotheses, and finally the conclusions and implications were made.